Perilaku Organisasi dan Peran Hubungan Masyarakat dalam Pemasaran Sekolah: Organizational Behavior and the Role of Public Relations in School Marketing - S. Adevia Ayu Kusumaning Putri; Erny Roesminigsih; Amrozi Khamidi; Mochamad Nursalim (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Organizational behavior and public relations (PR) play important roles in improving the performance and image of educational institutions. This study aims to analyze the relationship between organizational and human behavior in supporting the effectiveness of school marketing. The literature study method used a qualitative approach, and relevant data was obtained from various literature, such as books, journals, and scientific articles that discuss related topics. The study results indicate that organizational behavior characterized by effective collaboration, open communication, and transparent culture can improve human resource performance, which in turn helps build a positive image of educational institutions. In addition, the role of transformational leadership in creating an innovative and inspiring work environment has been shown to impact the effectiveness of marketing strategies significantly. This study also identifies the importance of using social media as one of the main tools in school marketing strategies. Through structured public relations management, social media promotes and builds strong relationships between schools, the community, and the external public. This strategy effectively attracts prospective students while strengthening educational institutions' reputation in the public's eyes. Thus, adaptive organizational behavior and innovative public relations communication strategies make a major contribution to supporting the achievement of school marketing goals. In conclusion, the synergy between good organizational behavior and the role of effective public relations can create competitive advantages for educational institutions amidst increasingly tight competition in the education sector.